Hematološka nujna stanja - Glaser Kraševac, Marjana (2020)
Hematological Emergencies. Acute life threatening hematological emergencies can occur in patients, suffering of benign blood disorders and hematological malignancies or they are a result of its treatment. They can occur as initial presentation of the disease or in a patient with established diagnosis. Furthermore there is a rapid development of new targeted drugs in hematology, and more hematology patients are treated aggressively despite comorbidities and higher age. This development will lead to an increase in the number of hematologic emergencies, and these patients will be seen by various physicians – from primary to the subspecial and intensive care. Therefore the knowledge of hematological emergencies is crucial for all physicians. This textbook deals with the most common hematological emergencies. Besides pathophysiology and clinical picture instructions for early diagnosis and treatment of these conditions are presented that can significantly affect the patient’s clinical outcome. Separate the possible traps, which can lead to false interpretation of the emergency, are highlighted.
Keywords: hematological emergencie; hematological malignancies; benign blood disorders; medicine; textbook